Klemensa Szaniawskiego metody sprawiedliwego podziału dóbr - Kuc, Marta (Filozofia Nauki, 2001)
Klemens Szaniawski has proposed two probabilistic principles of a just division of goods, based on postulates of egalitarism and optimum conditions: the principle of equal chances of satisfaction and the principle of equal chances of choice. The differences between these principles follow from a different understanding of the issue of equality, which leads to the differences in procedures and final results. When egalitarism is understood as the equality of chances of satisfaction, in many cases it cannot be reconciled with the postulate of optimum conditions. In the paper one can find some selected conclusions of the analyses of that issue and a comparison of the consequences of both principles: i.a. regarding the fulfilment of other criteria: proportionality and rightness.